2022
DOI: 10.48550/arxiv.2203.14695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recruiting Software Engineers on Prolific

Abstract: Recruiting participants for software engineering research has been a primary concern of the human factors community. This is particularly true for quantitative investigations that require a minimum sample size not to be statistically underpowered. Traditional data collection techniques, such as mailing lists, are highly doubtful due to self-selection biases. The introduction of crowdsourcing platforms allows researchers to select informants with the exact requirements foreseen by the study design, gather data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The pre-screened followed the same criteria. What was different is the competence screening, where we asked specific To ensure high data quality, we recruited participants from the academic data collection platform Prolific Academic and compensated participants above the US minimum wage (Palan and Schitter 2018;Russo 2022). The survey was run using Qualtrics.…”
Section: Softwarementioning
confidence: 99%
“…The pre-screened followed the same criteria. What was different is the competence screening, where we asked specific To ensure high data quality, we recruited participants from the academic data collection platform Prolific Academic and compensated participants above the US minimum wage (Palan and Schitter 2018;Russo 2022). The survey was run using Qualtrics.…”
Section: Softwarementioning
confidence: 99%
“…These historical sampling strategies raise concerns for generalizablity and and overall appropriateness of sample size. Recently, many researchers use paid platforms or other hosted sampling services and found that many of the same challenges sampling and recruiting appropriate and relevant participants and screen question challenges [10], [11]. Additional recent work aims to shed light on addressing recruitment challenges surrounding sampling, participant screening, and using student software engineers as proxies for full-time software developers [12]- [15].…”
Section: B Participant Recruitment In Software Engineering Researchmentioning
confidence: 99%